Bioecology of rubus species introduced to Uzbekistan - Ismanova Gulmira Shukhratjon's Qizi (Peerian Journals Publishing, 2022)
This article contains an article entitled "Bioecology of rubus species introduced to Uzbekistan", in which the species and genera of raspberries are introduced.
Keywords: Raspberry; type; category; variety